Acheulean in Monaco: Observatoire cave and its singular occupations. (8th August 2016) - Rossoni-Notter, Elena; Notter, Olivier; Simone, Suzanne; Simon, Patrick
Abstract: The Observatoire cave is located in the western end of the Principality of Monaco. Excavated very early – in 1916 – due to an event of an unexpected discovery, its lower unit, divided from c to k, delivered numerous assemblages including in particular handaxes, and more surprising, series of limestone large flakes and spherical pebbles. In the 1980's, new surveys were conducted and achieved a new layer (l) dated from 350 to 400ka (MIS 11-10). U–Th methods also gave two other dates within the stratigraphy: >178ka (>MIS 6) for stalagmitic floor II and >230ka (>MIS 7) for stalagmitic floor III. The oldest evidence of human occupations in Monaco – never studied in its integrality – deserved further and complete analysis of its successive assemblages. This work, based upon the use of unpublished archival data and a complete inventory and relocation of the pieces, provides precious and new information on the former "Old Paleolithic" filling. Petrographical, technotypological and morphofunctional analysis allowed highlighting the successive technoeconomic features. The correlation between the updated study of the industries coming from the old excavations and the unpublished results of the modern ones confirm the presence of a singular component (i–k units and l layer), out of the regional Paleolithic panorama. The lowest toolmakers selected subovoid and fist sized peripheral limestone pebbles, rarely andesitic, obviously for different in situ activities. They also shaped more voluminous and semi-local (?) limestone pebbles from which they imported standardized large flakes (≈100 × 100 mm) mostly used for their convex-cutting edge (cleaver). This specific and functional duo includes handaxes (k unit), pebble tools (l layer) and other products from few elaborated debitage made of semi-local (Ciotti) and allochtonous (Esterel, north of Var) siliceous materials. Consequently, it is considered within the Liguro-Provençal Acheulean panorama. The more recent knappers d–e–f-h1 left fewer traces (due to the function of their occupations?). They also rather favored the north peripheral (Ex-Vita) and ligurian (San Remo/Bordighera) areas while they employed more complex methods of debitage (Levallois recurrent unipolar, Levallois recurrent unipolar convergent, Levallois recurrent centripetal, unifacial/bifacial Discoid). In parallel of these productions (flakes, points and blades), shaping activities remained with the presence of two bifacial pieces (e unit) considered as support of tools, in contrast with the inferior bevel handaxe (k).